Expression of hormone receptors ERα, ERβ and PgR in HER-2-positive breast cancer - Litwiniuk, Maria (Contemporary Oncology/Współczesna Onkologia, 2007)
Background: HER-2/neu gene is amplified and overexpressed in 15–20% of invasive breast cancers. HER2-positive breast cancers have a worse prognosis than HER-2-negative tumors and distinctive clinical features. They express hormone receptors for estrogen (ERα) and for progesterone (PgR) less frequently than HER-2-negative tumors. The identification of the other human estrogen receptor, receptor beta (ERβ), raises a question of ERβ occurrence in HER-2-positive breast cancer. Materials and methods: Formalin-fixed, paraffin embedded tissues from 90 patients with invasive HER-2-positive breast cancer and from 99 patients with HER2-negative breast cancer were used in this study. The HER-2 status was analyzed using HercepTest TM (IHC), and IHC 2+ results were confirmed with FISH test. Immunostaining for ERα, ERβ and PgR was performed using monoclonal antibodies against ERα, PgR (DakoCytomation) and against ERβ (CHEMICON). The data were analyzed using nonparametric Fisher-Freeman-Halton test. Results: Only 33% of the HER2-positive breast cancers were ERα-positive compared with 62,6% in the HER2-negative group (p<0.001). The expression of ERα protein was observed in almost equal frequency in both groups (57% of HER2-positive breast cancers and 57.6% of HER2-negative tumors, p=0.889). The expression of PgR was observed in 30% of HER2-positive breast cancers and in 68.7% of HER2-negative tumors (p<0.001). Conclusion: The expression of ERβ (unlike that of ERα and PgR) was similar in HER-2-positive and in HER-2-negative breast cancers. Thus, ERβ may be a potential target in future endocrine therapy for women with HER2-positive breast cancers.